DAMPAK PERCERAIAN ORANGTUA TERHADAP PERKEMBANGAN EMOSIONAL DAN MINAT BELAJAR SISIWA KELAS VI DI SDN 61 KARARA KOTA BIMA - Pinkan; Ade S Anhar; Abdussahid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The impact of parental divorce on the behavior of elementary school-aged children is often quite significant, because they are at a very vulnerable stage of emotional and social development. Children who grow up in divorced families often experience emotional stress that can affect their behavior at school. Feelings of anxiety, anger, or confusion related to parental separation can cause children to exhibit aggressive behavior, be easily offended, or withdraw from social interactions. This study aims to analyze the impact of parental divorce on the emotional development and learning interests of grade VI students at SDN 61 Karara, Bima City. The method used is qualitative with a descriptive approach, with data collection techniques in the form of interviews, observations, and documentation, involving students, teachers, and parents as the main subjects. The results of the study indicate that parental divorce can cause emotional disturbances such as sadness, anxiety, loneliness, and loss of motivation, which directly affect students' learning interests and achievements. Conclusions from Parental divorce can cause emotional disturbances and decreased learning interests in grade VI students. Children often experience sadness, anxiety, and loneliness which have a negative impact on concentration and academic achievement. However, support from family, teachers, and the surrounding environment can help them recover and refocus on education. Therefore, the active role of schools and parents is very important in providing appropriate support.